2007
DOI: 10.1080/17450390701664314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrocolloidal silver nanoparticles on gastrointestinal microflora and morphology of enterocytes of quails

Abstract: The objective of the present study was to examine the effects of hydrocolloidal silver nanoparticles (Ag-nano) on microbial profile of caecum and morphology of enterocytes in duodenum of Japanese quail, as a model animal for poultry. Quails (Coturnix coturnix japonica) (10 d old) were randomly divided into four groups (15 quails each) and located into four cages for 12 days. Quails were fed with granulated diets given ad libitum and had free access to drinking water. Ag-nano were added to drinking water at con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 14 publications
8
65
1
2
Order By: Relevance
“…This lack of treatment effect is consistent with findings in quail, pigs, and chickens and supports the conclusion that AgNano do not affect growth [7,20,[23][24][25]. Interestingly, the difference in fat uptake between treatments was not reflected in hatchling development.…”
Section: Hatchling Developmentsupporting
confidence: 80%
“…This lack of treatment effect is consistent with findings in quail, pigs, and chickens and supports the conclusion that AgNano do not affect growth [7,20,[23][24][25]. Interestingly, the difference in fat uptake between treatments was not reflected in hatchling development.…”
Section: Hatchling Developmentsupporting
confidence: 80%
“…histolyticum group was reduced with 20 ppm silver (P = 0.012). In the same way, Sawosz et al (2007) did not observed a major effect of colloidal silver on bacterial concentration in the digestive tract of quails, but only a significant increase in lactic acid bacteria was observed with 25 ppm. Results on productive performances in several experiments with pigs and poultry carried out by our group were variable (Table 1): a numerical increase in daily growth was generally observed when 20 ppm silver were added compared with the control (no silver), but this effect was not generally significant.…”
Section: Potential Use Of Silver In Animal Feedingsupporting
confidence: 49%
“…33 More and more results provide evidence for a molecular mechanism of nano-Ag activity, showing that nano-Ag act through reactive oxygen species generation, 29 leading to activation of proteins and inducing apoptosis via the mitochondrial pathway. 34 In vivo measurements in chicken embryos and quails demonstrated that hydrocolloids of nano-Ag at the level of 50 ppm did not affect development or cause oxidative DNA damage to embryos 35 or growth of quails. 36 Gold nanoparticles (nano-Au) are well established carriers for delivery of double-stranded DNA in gene gun technology.…”
Section: Introductionmentioning
confidence: 99%